The political economy of ecofeminist degrowth - Houtbeckers, Eeva (Syddansk Universitetsforlag, 2025)
Socio-ecological crises pose numerous problems for the continuity of human communities and morethan- human beings. First, previous thinkers have shown how capitalism and continuous economic growth are tightly linked, which has led to overproduction and overconsumption. Second, ecofeminists point out that not everyone is responsible for these crises. Furthermore, dualist and hierarchical mindsets maintain the exploitation of women, minorities, and more-than-human beings. Bridging these two debates is important to dismantling gendered economic exploitation on the one hand and the capitalist growth economy on the other. This text briefl y introduces the history of ecofeminism and the ecofeminist political economy. It also identifi es themes in ecofeminist degrowth thinking by analysing the works of Ariel Salleh and Stefania Barca. It is important to highlight ecofeminist thinking so that current degrowth debates do not ignore the institutionalised exploitation of women, minorities, and other species in economic activity.